How much are we spending? The estimation of research expenditures on cardiovascular disease in Canada - de Oliveira Claire; Nguyen Van; Wijeysundera Harindra C; Wong William W L; Woo Gloria; Liu Peter P; Krahn Murray D (BMC, 2012)
Abstract Background Cardiovascular disease (CVD) is a leading cause of death in Canada and is a priority area for medical research. The research funding landscape in Canada has changed quite a bit over the last few decades, as have funding levels. Our objective was to estimate the magnitude of expenditures on CVD research for the public and charitable (not-for profit) sectors in Canada between 1975 and 2005. Methods To estimate research expenditures for the public and charitable sectors, we compiled a complete list of granting agencies in Canada, contacted each agency and the Canadian Institutes of Health Research (CIHR), and extracted data from the organizations' annual reports and the Reference Lists of health research in Canada. Two independent reviewers scanned all grant and fellowship/scholarship titles (and summary/key words, when available) of all research projects funded to determine their inclusion in our analysis; only grants and fellowships/scholarships that focused on heart and peripheral vascular diseases were selected. Results Public/charitable sector funding increased 7.5 times, from close to $13 million (in constant dollars) in 1975 to almost $96 million (in constant dollars) in 2005 (base year). The Medical Research Council of Canada (MRCC)/CIHR and the Heart & Stroke Foundation of Canada have been the main founders of this type of research during our analysis period; the Alberta Heritage Foundation for Medical Research and the Fonds de la recherche en santé du Quebec have played major roles at the provincial level. The Indirect Costs Research Program and Canada Foundation for Innovation have played major roles in terms of funding in the last years of our analysis. Conclusion Public/charitable-funded research expenditures devoted to CVD have increased substantially over the last three decades. By international standards, the evidence suggests Canada spends less on health-related research than the UK and the US, at least in absolute terms. However, this may not be too problematic as Canada is likely to free-ride from research undertaken elsewhere. Understanding these past trends in research funding may provide decision makers with important information for planning future research efforts. Future work in this area should include the use of our coding methods to obtain estimates of funded research for other diseases in Canada.